Synthesis and Antimicrobial Evaluation of Potent 6H-2-Amino-4,6-diaryl-1,3-thiazines - BASKAR, G.; GOPALAKRISHNAN, M.; WINFRED JABARAJ, J. (Asian Journal of Chemistry, 2010)
In a ethanolic solution of 3′,5′-dichloro-2′-fluorochalcone (1a) and thiourea (2) when refluxed with aq. KOH for 5 h 6H-2-amino-4,6-diaryl-1,3-thiazines is formed. Likewise the chalcones 1b, 1c and 1d give the respective thiazines 5b, 5c and 5d. The products are analyzed by 1H and 13C NMR spectra. The products are tested for antibacterial and antifungal activity.